2018
DOI: 10.1007/s10514-018-9764-z
|View full text |Cite
|
Sign up to set email alerts
|

A dynamical system approach to task-adaptation in physical human–robot interaction

Abstract: The goal of this work is to enable robots to intelligently and compliantly adapt their motions to the intention of a human during physical Human-Robot Interaction (pHRI) in a multi-task setting. We employ a class of parameterized dynamical systems that allows for smooth and adaptive transitions between encoded tasks. To comply with human intention, we propose a mechanism that adapts generated motions (i.e., the desired velocity) to those intended by the human user (i.e., the real velocity) thereby switching to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 56 publications
0
78
0
Order By: Relevance
“…How should a contact robot be controlled to provide a stable and appropriate response to a user with unknown dynamics during various activities ranging from sport training, to physical rehabilitation and shared driving [8,9,10]? Specific human-robot interactions have been studied [11,12] but a general framework for interactive control is still missing. It has been suggested that differential game theory (GT) can be used as a framework to describe various interactive behaviors between a robot and its human user [13].…”
Section: Introductionmentioning
confidence: 99%
“…How should a contact robot be controlled to provide a stable and appropriate response to a user with unknown dynamics during various activities ranging from sport training, to physical rehabilitation and shared driving [8,9,10]? Specific human-robot interactions have been studied [11,12] but a general framework for interactive control is still missing. It has been suggested that differential game theory (GT) can be used as a framework to describe various interactive behaviors between a robot and its human user [13].…”
Section: Introductionmentioning
confidence: 99%
“…Methods combining machine learning and dynamical systems, e.g. [58] could be investigated as they could also encompass the planning part.…”
Section: Discussionmentioning
confidence: 99%
“…In the second scenario, we perform a collaborative task with a human where the human asks the robot to clean the surface at different locations. To achieve this, we combine the proposed force adaptation with a mechanism to adapt the attractor of a nominal limit cycle (proposed in our previous works [22], [31]). We show that the force modulation can adapt fast enough to cope with the change in dynamics.…”
Section: Experimental Evaluationsmentioning
confidence: 99%
“…• The work in [31] to switch across different tasks. For the cleaning of the surface we define two tasks: -The homing task (i = 1) defined by f 1 (x) = x a,h − x and F 1 d (x) = 0 ∀x, where the robot should reach a fixed attractor above the surface, with x a,h the attractor.…”
Section: B Collaborative Cleaning Of a Non-flat Surfacementioning
confidence: 99%
See 1 more Smart Citation